2009
DOI: 10.1016/j.apcata.2009.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Citrate or hydrotalcite?

Abstract: Trace amounts of Pt-and Ru-doped Ni/Mg(Al)O catalysts were prepared by a citrate method and tested in the oxidative reforming of C 3 H 8 under daily start-up and shutdown (DSS) operation. The activity and the sustainability of the catalysts were compared with those of the Pt-and Ru-doped Ni/Mg(Al)O catalysts derived from hydrotalcite (HT) precursor. The DSS operation of C 3 H 8 reforming was carried out with O 2 gas or O 2 /H 2 O mixed gas between 200 ºC and 600 or 700 ºC under air purging conditions. The cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Takehira et al [44] reported that Pt or Ru doped Nibased catalyst prepared from Mg-Al hydrotalcite-like anionic clay with citrate method showed high and stable activity for steam reforming of propane. Dreyer et al [45] studied autotherrmal steam reforming of higher hydrocarbons such as n-decane, n-hexadecane and JP-8 over Rh-coated monolith.…”
Section: Noble Metals Loaded Hydrotalcitesmentioning
confidence: 99%
“…Takehira et al [44] reported that Pt or Ru doped Nibased catalyst prepared from Mg-Al hydrotalcite-like anionic clay with citrate method showed high and stable activity for steam reforming of propane. Dreyer et al [45] studied autotherrmal steam reforming of higher hydrocarbons such as n-decane, n-hexadecane and JP-8 over Rh-coated monolith.…”
Section: Noble Metals Loaded Hydrotalcitesmentioning
confidence: 99%